Tanggung Jawab Penyedia Jasa Fast Boat terhadap Konsumen Saat Terjadi Kecelakaan di Desa Kusamba Kabupaten Klungkung (Studi Pada PT. Sekarjaya) - Kadek Rizky Aditya Indrabuana; I Nyoman Putu Budiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
The background writing this thesis responsibility of fast boat providers to consumers when an accident occurs. Given the importance of the role of transportation, especially sea transportation, activities related to sea transportation need regulated by the state, sea transportation activities can be carried out in an orderly manner and protect interests of the parties involved. However, sea transportation is not always available properly, because not rule out the possibility of things that are detrimental to the users of sea transportation. Based on this, the problem this thesis is how fast boat are responsible for consumers are harmed in the event of accident and how implement fulfillment of compensation for passengers in an accident at PT. Sekar Jaya. The research method used is empirical legal research. The results showed the responsibility of the carrier an accident occurs, PT Sekar Jaya as a shipping company is responsible for maintaining the safety, and responsible replacing losses arising from accidents. The implementation fulfillment of compensation for passengers have accident can come directly to PT Jasa Raharja to claim compensation by filling out the compensation application form provided PT Jasa Raharja attaching a description of the accident, health information from doctors, hospitals and personal identification.